2014
DOI: 10.1371/journal.pone.0095008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin E Supplementation on Glycaemic Control: A Meta-Analysis of Randomised Controlled Trials

Abstract: Observational studies have revealed that higher serum vitamin E concentrations and increased vitamin E intake and vitamin E supplementation are associated with beneficial effects on glycaemic control in type 2 diabetes mellitus (T2DM). However, whether vitamin E supplementation exerts a definitive effect on glycaemic control remains unclear. This article involves a meta-analysis of randomised controlled trials of vitamin E to better characterise its impact on HbA1c, fasting glucose and fasting insulin. PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 44 publications
7
70
0
9
Order By: Relevance
“…We could not see the beneficial effects of other antioxidants; eicosapentaenoic acid (59), or VE (63,65) with/without AA on FBS, this finding was similar to results obtained by previous metaanalysis in diabetics (13,101).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We could not see the beneficial effects of other antioxidants; eicosapentaenoic acid (59), or VE (63,65) with/without AA on FBS, this finding was similar to results obtained by previous metaanalysis in diabetics (13,101).…”
Section: Discussionsupporting
confidence: 89%
“…Several epidemiological studies have shown that individuals with low concentration of antioxidants are at increased risk of diabetes complications (8,9). Recently, Xu et al (13) published the effect of vitamin E (VE) supplementation on diabetes improvement. Along with their work, we aimed to critically and systematically, assess the effect of ascorbic acid (AA) in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, interstudy heterogeneity led to further subgroup analysis, which revealed a significant reduction in HbA1c in hypovitaminosis E T2DM patients following supplementation 89. However, as noted by the authors, the small datasets involved in this subgroup analysis mean further studies are required to corroborate this finding before any recommendations can be made.…”
Section: Erythrocyte Turnovermentioning
confidence: 82%
“…Vitamin E intake may reduce glucose levels in type 2 diabetics and in subjects with baseline serum vitamin E deficiencies . High doses of vitamin E (>400 IU d –1 ) supplemented for longer periods (>12 weeks) significantly reduced HbA1c levels and fasting insulinemia …”
Section: Discussionmentioning
confidence: 99%